Mapping ecologically important virus-host interactions in geographically diverse solar salterns with metagenomics - Moller,Abraham G; Liang,Chun (PeerJ Preprints, 2016)
Solar salterns are excellent model ecosystems for studying virus-microbial interactions because of their low microbial diversity, environmental stability, and high viral density. By using the power of CRISPR spacers to link viruses to their prokaryotic hosts, we explored virus-host interactions in geographically diverse salterns and related them to carbon cycling. Using taxonomic profiling, we identified hosts such as archaeal Haloquadratum, Halorubrum, and Haloarcula and bacterial Salinibacter, and we found that community composition related to not only salinity but also local environmental dynamics. Characterizing glycerol metabolism genes in these metagenomes suggested most dihydroxyacetone kinase genes affiliate to Halorubrum and Haloquadratum while most glycerol-3-phosphate dehydrogenase genes affiliate to Salinibacter. We identified CRISPR spacers in the metagenomes with two different methods and found more spacers in the Halobacteriaceae-dominated IC21 and C34 salterns compared with the Haloquadratum-dominated SS19, SS33, and SS37 salterns, suggesting low CRISPR diversity and possibly a high rate of CRISPR loss in the Haloquadratum-dominated salterns. After CRISPR detection, spacers were aligned against haloviral genomes to map virus to host. While most alignments linked viruses to Haloquadratum walsbyi, there were clusters of interactions with less abundant Haloarcula and Haloferax. Further examination of the dimer and codon usage differences between paired viruses and their hosts and detection of cas genes in the salterns confirmed both the plausibility of virus-host interactions and the possibility of CRISPR activity. Taken together, our studies suggest CRISPR loss in archaeal hosts controls the level of virus proliferation and the nutrient turnover viruses induce in these environments.
Keywords: CRISPR; hypersaline ecosystems; metagenomics; microbial ecology; halophiles; viral shunt; bioinformatics; extremophiles; environmental genomics; viruses